1999
DOI: 10.1017/s0952523899166136
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differentiation of bipolar cells in the ferret retina

Abstract: Bipolar cells are not only important for visual processing but input from these cells may underlie the reorganization of ganglion cell dendrites in the inner plexiform layer (IPL) during development. Because little is known about the development of bipolar cells, here we have used immunocytochemical markers and dye labeling to identify and follow their differentiation in the neonatal ferret retina. Putative cone bipolar cells were immunoreacted for calbindin and recoverin, and rod bipolar cells were immunostai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 51 publications
4
33
0
Order By: Relevance
“…In line with this idea, recent studies have shown that the axon terminals of On-and Off-cone bipolar cells form their stratified projection patterns in a remarkably precise manner, without any initial period of intermingling (Miller et al, 1999;Günhan-Agar et al, 2000). Moreover, electrophysiological recordings have reported that very few ganglion cells in the developing cat retina respond with On-Off discharges to flashing spots of light at a time when multistratified cells would be expected to be plentiful (Dubin et al, 1986;Tootle, 1993).…”
mentioning
confidence: 82%
“…In line with this idea, recent studies have shown that the axon terminals of On-and Off-cone bipolar cells form their stratified projection patterns in a remarkably precise manner, without any initial period of intermingling (Miller et al, 1999;Günhan-Agar et al, 2000). Moreover, electrophysiological recordings have reported that very few ganglion cells in the developing cat retina respond with On-Off discharges to flashing spots of light at a time when multistratified cells would be expected to be plentiful (Dubin et al, 1986;Tootle, 1993).…”
mentioning
confidence: 82%
“…The biological mechanism had to be distinct from eye opening, which does not occur until P13. Several reports have suggested that the maturation of the photoreceptor-bipolarganglion cell pathway occurs close to P10 (Miller et al, 1999) and that glutamate receptors begin to play a prominent role in driving retinal activity by P11 (Bansal et al, 2000). To test whether this maturation of the glutamatergic pathway in the retina was necessary for the activation of CaN in the sSC, we reduced retinal glutamatergic activity in vivo and assayed the effects on NMDAR currents in sSC neurons.…”
Section: Retinal Ganglion Cell Activity Is Necessary For the Can-indumentioning
confidence: 99%
“…Functional studies of the resulting mature visual system reveal that this pharmacologic manipulation leads to a dramatic increases in the number of RGCs that permanently exhibit both ON and OFF responses to light (Bisti et al, 1998). However, a significant percentage of RGCs stratify into ON/OFF sublaminae before bipolar cells-the source of glutamate to RGCs-have made functional synapses in the IPL (Miller et al, 1999). What then drives the initial RGC dendritic segregation?…”
Section: Role Of Nachr-mediated Waves In Retina Developmentmentioning
confidence: 99%
“…At the earliest stages of development when processes can first be detected with immunohistochemical markers, both bipolar cell (Miller et al, 1999) and cholinergic amacrine cell (West Greenlee et al, 1998) processes appear stratified. A recent study in rats has also demonstrated that bipolar cell stratification is normal in the absence of RGCs (Gunhan-Agar et al, 2000).…”
Section: Role Of Nachr-mediated Waves In Retina Developmentmentioning
confidence: 99%